Differential Equations with Fuzzy Uncertainty - Chakraverty, Snehashish; Mahato, Nisha; Karunakar, Perumandla; Dilleswar Rao, Tharasi (Advanced Numerical and Semi-Analytical Methods for Differential Equations, 2019)
This chapter explains a system of fuzzy linear differential equations. Recently, a new technique using the triangular fuzzy numbers (TFNs) is illustrated to model the fuzzy linear differential equations. The solution of linear differential equations with fuzzy initial conditions may be studied as a set of intervals by varying α‐cut. A geometric approach to solve fuzzy linear systems of differential equations have been studied by Gasilov. The difference between this method and the methods offered to handle the system of fuzzy linear differential equation is that at any time the solution consists a fuzzy region in the coordinate space. The chapter presents a procedure to solve fuzzy linear system of differential equations. There exist various types of fuzzy numbers and among them the TFN is found to be mostly used by different authors. One can observe the TFN solutions for different α‐cuts at any time t.